Estimación de la demanda en publicaciones periódicas con múltiples puntos de venta y stockouts infrecuentes - Jose Mari Eguzkitza Arrizabalaga (Colegio de Economistas de A Coru\~na, 2007)
– Historical sales and demand are not equivalent when referred to periodicals, since the former are limited by the available stock. When the mean stockout is low and there is not possibility of updating data during the selling period, demand is estimated by means of a maximum-likelihood procedure. The paper also reports another practical approach wich consists of estimating the lack of issues per out-of-stock period and per point-of-sale. In order to compare both methods, real data on sales of a monthly periodical from Bizkaia are used. The results obtained after using the approximate method do practically coincide with those obtained after using the maximum-likelihood procedure. Moreover, computations were much simpler.
Keywords: 330; Zeitung; Nachfrage; Theorie